Compact highly integrated wide-tunable unidirectional dual-band patch antenna for wireless applications - Boukarkar, Abdelheq; Lin, Xian Qi; Jiang, Yuan; Yu, Yi Qiang (IET microwaves, antennas & propagation, 2017)
A compact dual-band patch antenna with independent tuning of both frequencies is introduced. The frequency agility is achieved by inserting two varactor diodes into the radiating patch, while the antenna miniaturisation is realised by shorting one patch edge using metallised vias. Simulated and measured results are in good agreement. Measurements reveal that the two operating bands can be tuned separately without any frequency shifting and with high stability and similar unidirectional radiation patterns during the tuning process. The measured tunable ranges of the lower and upper bands are 27.95% (from 2.4 to 3.18 GHz) and 28.27% (from 4.1 to 5.45 GHz), with measured peak gains and efficiencies of [3.23 dBi, 65%] and [3.42 dBi, 62%], respectively. The antenna presents comparatively wide tuning ranges with similar unidirectional radiation patterns, has a miniaturised size, and uses a simple direct current bias circuit. Thus, it can be easily integrated and used in different wireless systems.